Transformations : women, gender & psychology - Crawford, Mary 4 0 (Mary E.)16; 5 (New York : McGraw-Hill, 2012)
Transformations presents a broad, comprehensive theoretical framework for understanding how the lives of all people, but particularly the lives of girls and women, are shaped by gender. Rather than conceiving gender as a collection of individual traits or attributes, this book presents gender as a social system that is used to categorize people and is linked to power and status. The gender system is analyzed throughout the book at three levels: sociocultural, interpersonal, and individual. Because conceptualizing gender as a social system is important from the start, the second chapter of the book is devoted to gender, status, and power. This chapter explains the gender system and how it works at each of the three levels and demonstrates how they are linked--
Pt. 1. Paving the way. Beginnings -- What is feminism? -- Methods and values in psychological research.;Pt. 2. Gender in social context. Gender, status, and power -- Images of women -- The meanings of difference.;Pt. 3. Gender and development. Sex, gender, and bodies -- Gendered identities : childhood and adolescence.;Pt. 4. Gendered life paths. Sex, love, and romance -- Commitments : women and close relationships -- Mothering -- Work and achievement -- The second half : midlife and aging.;Pt. 5. Gender and well-being. Violence against women -- Psychological disorders, therapy, and women's well-being -- Making a difference : toward a better future for women.
Machine generated contents note: Part 1. INTRODUCTION 1. Paving the Way Part 2. GENDER IN SOCIAL CONTEXT 2. Gender, Status, and Power 3. Images of Women 4. The Meanings of Difference Part 3. GENDER AND DEVELOPMENT 5. Sex, Gender and Bodies 6. Gendered Identities: Childhood And Adolescence 7. Sex, Love, and Romance Part 4. GENDERED LIFE PATHS 8. Commitments: Women and Close Relationships 9. Mothering 10. Work and Achievement 11. The Second Half: Midlife and Aging Part 5. GENDER AND WELL-BEING 12. Violence Against Women 13. Psychological Disorders, Therapy, and Women's Well-Being 14. Making a Difference: Toward a Better Future for Women.
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Psychology. -- Women;Gender identity.;Feminist psychology.;Sex role.;Sex differences (Psychology);Social change. -- 20; 20; 2